Pembuatan Sistem Desalinasi Kapasitas 240 liter/jam di Dusun Bondan Kecamatan Kampung Laut Cilacap - Bayu Aji Girawan; Agus Santoso; Joko Setia Pribadi; Supriyono Supriyono (Madani : Indonesian Journal of Civil Society, 2022)
Dusun Bondan is a district located in a tidal area. Various problems arise in Dusun Bondan because of the use of water that doesn’t meet the quality of sanitation water causing several diseases. The water crisis experienced by the residents of Dusun Bondan becomes the worst disaster especially in summer because the water at Dusun Bondan is salty with high total dissolved solids. A water desalination system has been made to produce sanitation water that meets the standard based on Minister of Health Regulation No. 32 of 2017. The methods used to overcome these problems are water source identification, design of desalination system, purchasing, fabrication and testing of desalinated water. The result of the activities is a desalination system which consists of pre-treatment using 4 filtration stages ended with reverse osmosis desalination using a special membrane. The result of desalinated water test shows that the water is odourless, tasteless, and other parameters meet the requirement of the standard.